The Effect of Spiritual Intelligence and Social Competence on the Performance of Middle School Teachers in Sinaboi District, Rokan Hilir Regency - Lazrina Lazrina; Suarman Suarman; Sri Kartikowati (Journal of Educational Sciences, 2022)
Some of the problems with the performance of elementary school teachers in Cluster V, Rupat District, such as teachers who have not been able to make the class situation calm when there are students making noise in class, there are still teachers who have not made learning preparations before teaching, lack of teacher initiative in using learning media, methods teacher learning is very monotonous, namely by reading book texts, and there are still many teachers who do not understand and carry out school administration such as teachers who do not have a plan about the learning process according to their grade level. The location where this research was carried out was in Rupat District, Bengkalis Regency, Riau Province. The population of this study were public elementary school teachers totaling 67 people. The sampling technique used a saturated sample. So the number of samples used in this study were 67 teachers. A jointly significant effect was obtained between the Discipline and Motivation variables on teacher performance of 99.4% with a very high interpretation, because there were still 0.6% determined by other factors that were not part of this study. This effect is illustrated by each increase in one unit of Discipline of 0.217 and an increase of one unit in Motivation of 0.788, it will be followed by an increase in teacher performance of 2.781 one unit.